Oxidation state of bioavailable dissolved organic matter influences bacterioplankton respiration and growth efficiency - Brandon M. Stephens; Paolo Stincone; Daniel Petras; Chance J. English; Keri Opalk; Stephen Giovannoni; Craig A. Carlson (Communications Biology)
Abstract Oxygen consumption by oceanic microbes can predict respiration (CO2 production) but requires an assumed respiratory quotient (RQ; ΔO2/ΔCO2). Measured apparent RQs (ARQs) can be impacted by various processes, including nitrification and changes in dissolved organic matter (DOM) composition, leading to discrepancies between ARQ and actual RQ. In DOM remineralization experiments conducted in the eastern North Atlantic Ocean, ARQs averaged 1.39 ± 0.14, similar to predictions for complete consumption of plankton biomass. DOM removed with an elevated nominal oxidation state (i.e., more oxidized DOM), as detected by liquid chromatography-tandem mass spectrometry, coincided with increased hydrolyzable amino acid removal, increased ARQs and bacterioplankton respiration (BR), and a decreased bacterioplankton growth efficiency (BGE). Across experiments, evidence emerged that nitrification and DOM partial oxidation, driven in part by bacterioplankton members of OM43, SAR92 and Rhodobacteraceae, can elevate BR relative to bacterioplankton consumption of plankton-derived carbon. These rare synoptic measurements of interrelated variables reveal complex biochemical and cellular processes underlying variability in large-scale CO2 production estimates.